City Benchmarking, Globalized Urban Scholarship and the View from Above: Reflections on a Few Absences. (20th February 2021) - Robin, Enora
Abstract: In this short response I address Acuto et al .'s proposition to engage with the political economy of city benchmarking and rankings in order to show that critical urban scholarship can do better than 'limiting itself to criticism'. I argue that such engagement would require deeper reflexion on the political economy of critical urban scholarship itself and the style of research needed. I also discuss the extent to which this engagement with cities' comparative imagination as performed through benchmarks, rankings and indices runs the risk of overlooking other forms of global comparative endeavours happening outside of international urban solutions forums.